A new species of Parastenocaris from Mindoro Island, Philippines: Parastenocaris distincta sp. nov. (Crustacea: Copepoda: Harpacticoida: Parastenocarididae) - Cottarelli, Vezio; Bruno, Maria C.; Berera, Raffaella (Zootaxa, 2006)
A new species of harpacticoid, Parastenocaris distincta sp. nov., is described and discussed. The new species was collected in a freshwater interstitial habitat near the mouth of a river in Western Mindoro Province, the Philippines. This is the second species of Parastenocaris described from this country. The medial ornamentation of P1 basis, the morphology of male P3 and the number and distribution of the integumental pores in the new species differ from those previously reported in other species of Parastenocaris. We review and discuss the more common arrangements of these features in recently described species, emphasizing the taxonomic discriminative value of their variations.